2020
DOI: 10.35188/unu-wider/2020/917-4
|View full text |Cite
|
Sign up to set email alerts
|

Special economic zones in Southern Africa: white elephants or latent drivers of growth and employment? The case of Zambia and South Africa

Abstract: The successful use of special economic zones as economic tools for export-led industrial development in East Asia propelled a wave of similar initiatives across Africa. In Southern Africa, Zambia and South Africa instituted special economic zones in their respective legal and institutional frameworks in the 2000s as mechanisms for catalysing industrialization and employment creation by means of domestic and foreign investments. Using a case-study approach, we find that special economic zones in the Eastern Cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…An SEZ in Zambia cost US$230 million from 2010 to 2018, and attracted projects worth US$245 million in the same period. By 2040, it is expected to cost the state US$1.2 billion (Phiri and Manchishi 2020). Zambia abruptly eliminated income tax incentives for SEZs in 2018 on the grounds that the costs to the fiscus outweighed the benefits.…”
Section: Sezs In Southern Africamentioning
confidence: 99%
See 3 more Smart Citations
“…An SEZ in Zambia cost US$230 million from 2010 to 2018, and attracted projects worth US$245 million in the same period. By 2040, it is expected to cost the state US$1.2 billion (Phiri and Manchishi 2020). Zambia abruptly eliminated income tax incentives for SEZs in 2018 on the grounds that the costs to the fiscus outweighed the benefits.…”
Section: Sezs In Southern Africamentioning
confidence: 99%
“…According to the World Bank (2020), a survey found that reliable electricity was critical for company decisions on investment locations. Yet SEZs across Southern Africa faced regular load-shedding by national grids in the late 2010s (Phiri and Manchishi 2020). In effect, states are not willing to prioritize the SEZs to the extent of exempting them from load-shedding, which would effectively increase the burden on the rest of the economy or on households.…”
Section: Impacts On Sez Policiesmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Involvement of the private sector in this initiative is significant, and Kafue Steel sees itself as playing a lead strategic role in driving this process. 16 Compared to Zambia, South Africa's relative success in attracting investments from MNCs in manufacturing activities has been anchored in attaching supply chains to specific economic zone regions, a process that is in its nascent stages in Zambia (Phiri and Manchishi 2020).…”
Section: Funding and Industrial Policy Supportmentioning
confidence: 99%